2004
DOI: 10.1142/s0192415x04002107
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tai Chi Exercise on Physical and Mental Health of College Students

Abstract: The purpose of this pilot study is to examine the effects of Tai Chi Quan, a body-mind harmony exercise, on college students' perceptions of their physical and mental health. A three-month intervention of Tai Chi exercise was administered to college students, and multidimensional physical (PHD) and mental (MHD) health scores were assessed using the SF-36v2 health survey questionnaire before and after the intervention. Thirty college students participated in a 1-hour-long Tai Chi exercise intervention twice a w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(69 citation statements)
references
References 6 publications
5
61
0
3
Order By: Relevance
“…Of these 20, three studies were rejected because the intervention was a combination of exercises, did not mainly comprise TC exercises, or was not clearly described, whereas three other studies were not included because psychological health was not the main outcome. Thus, details of 14 studies are presented according to study design in Tables 3 and 4 [3,[25][26][27][28][29][30][31][32][33][34][35][36][37][38]. A total of eight randomized controlled studies and six nonrandomized ones were, thus, considered in this analysis.…”
Section: Analysis Of the Psychological Effects Of Tai Chi Practicementioning
confidence: 99%
See 1 more Smart Citation
“…Of these 20, three studies were rejected because the intervention was a combination of exercises, did not mainly comprise TC exercises, or was not clearly described, whereas three other studies were not included because psychological health was not the main outcome. Thus, details of 14 studies are presented according to study design in Tables 3 and 4 [3,[25][26][27][28][29][30][31][32][33][34][35][36][37][38]. A total of eight randomized controlled studies and six nonrandomized ones were, thus, considered in this analysis.…”
Section: Analysis Of the Psychological Effects Of Tai Chi Practicementioning
confidence: 99%
“…This is also among such population that research has shown tangible results. Few nonrandomized studies have targeted TC effects on younger and middle-aged people [26,27,30]. However, the effects noted should be interpreted cautiously considering the lack of information on the description of the experimental settings and interventions used.…”
Section: Commentarymentioning
confidence: 99%
“…Wang et al [4] by Taiji training, the content of serum IgG female college students than the control group, and IgM, IgA was no significant difference. Liu Yan ring [5] found that tai chi exercise can improve female students IgA and IgG levels.…”
Section: Adaptations Of Aerobic Exercise Plus Immunoglobulin Stop Tramentioning
confidence: 88%
“…Bei Taiji - auch «Tai Chi» oder «Tai Chi Chuan» geschrieben - handelt es sich um eine achtsam und überwiegend langsam auszuübende Bewegungsform, die ihren Ursprung in den chinesischen Kampfkünsten hat. Wie klinische Studien nahelegen, kann regelmässiges Ausüben von Taiji zu einer signifikanten Verbesserung des körperlichen und psychischen Wohlbefindens der Praktizierenden führen und das subjektive Stressempfinden mindern [5,6,7]. Zur Untersuchung der ressourcenaktivierenden und stressprotektiven Wirkung von Taiji wurden während der vergangenen 4 Jahre an der Kollegialen Instanz für Komplementärmedizin (KIKOM) der Universität Bern diverse Forschungsarbeiten durchgeführt.…”
Section: Hintergrundunclassified